2008
DOI: 10.1176/appi.neuropsych.20.3.309
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Dysfunctions Associated With PTSD: Evidence from World War II Prisoners of War

Abstract: The authors aim to delineate cognitive dysfunction associated with posttraumatic stress disorder (PTSD) by evaluating a well-defined cohort of former World War II prisoners of war (POWs) with documented trauma and minimal comorbidities. The authors studied a cross-sectional assessment of neuropsychological performance in former POWs with PTSD, PTSD with other psychiatric comorbidities, and those with no PTSD or psychiatric diagnoses. Participants who developed PTSD had average IQ, while those who did not devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 37 publications
2
17
0
2
Order By: Relevance
“…This is consistent with previous reports that low IQ is a risk factor for PTSD (Engelhard, van den Hout, & Schouten, 2006;Parslow & Jorm, 2007). Of particular relevance to the present data is a study of World War n veterans using the same instruments as those reported here that found that WTAR scores correlated with clinician ratings of PTSD severity on the basis of the CAPS (Hart et al, 2008). Likewise, our finding that premorbid ability was associated with severity of postconcussive complaints may be interpreted as evidence (hat premorbid factors place veterans al risk for PCD.…”
Section: Discussionsupporting
confidence: 93%
“…This is consistent with previous reports that low IQ is a risk factor for PTSD (Engelhard, van den Hout, & Schouten, 2006;Parslow & Jorm, 2007). Of particular relevance to the present data is a study of World War n veterans using the same instruments as those reported here that found that WTAR scores correlated with clinician ratings of PTSD severity on the basis of the CAPS (Hart et al, 2008). Likewise, our finding that premorbid ability was associated with severity of postconcussive complaints may be interpreted as evidence (hat premorbid factors place veterans al risk for PCD.…”
Section: Discussionsupporting
confidence: 93%
“…Also, we included both PTSD samples from Hart et al (2008) and both PTSD samples from Samuelson et al (2006), as both studies presented one PTSD sample with psychiatric comorbidities and one without. Studies that included symptom provocation or trauma recall in the same session as the administration of neuropsychological tests were included only if neuropsychological testing occurred before any potential symptom exposure.…”
Section: Methodsmentioning
confidence: 99%
“…For example, persons with PTSD tend to perform worse on some tests of executive functioning with moderate to large effect sizes (0.70-1.62) for Trails B reported in several studies (e.g., Beckham, Crawford, & Feldman, 1998;Jenkins. Langlais, Delis, & Cohen, 2000;Hart et al, 2008). Memory deficits in PTSD have been the focus of two 882 ANNE L. SHANDERA-OCHSNER ET AL.…”
Section: Ptsdmentioning
confidence: 99%